Isolation of GhMYB9 gene promoter and characterization of its activity in transgenic cotton - Z. Y. Zhang; J. Zhao; Y. Hu; T. Z. Zhang (Biologia Plantarum, 2015)
The GhMYB9 encodes a R2R3 MYB transcription factor in the upland cotton (Gossypium hirsutum L.) genome. Our studies show that GhMYB9 predominantly expressed in flowers and fibers. To gain a better understanding of its regulatory mechanism, we isolated the 5'-flanking region of GhMYB9 which was 1 487 bp in length. The cis-acting element prediction shows that this region contained the basic structure of the core promoter elements (TATA-box, CAAT-box) and the transcription start site (TSS). Other motifs, such as defense and stress responsiveness (TC-rich repeats), anaerobic induction (ARE), and MYB binding sites involved in drought-inducibility (MBS), were also found. Histochemical assay shows that the GhMYB9 promoter governed β-glucuronidase (GUS) expression mainly in seeds, fibers, and flowers of transgenic cotton. Also, the activity of the promoter was induced by auxin in fibers of transgenic cotton. This is consistent with its transcript abundance in different tissues. A further deletion analysis confirms that a promoter region from -1 231 to -860 was required for auxin response. Our findings provide a useful reference for the understanding of the transcriptional regulation mechanism of the GhMYB9 gene.